A phantom for the quantitative determination and improvement of the spatial resolution in slice-selective 2D-FT magnetic resonance micro-imaging and -microscopy based on Deep X-ray Lithography (DXRL) - Berg, Andreas Georg; Börner, Martin (Frontiers in Physics, 2023)
Introduction: The most important assessed quality-control (QC) criteria for improvements in high-resolution imaging are represented by the contrast-to-noise-ratio and spatial resolution. Ultra-High-Field (UHF) Magnetic-Resonance-scanners (B ≥ 7 T) for medical research allowed for the improvement in spatial resolution up to the microimaging and nominal microscopy range [pixel-size: ps < (100 μm)2], even in-vivo on humans just recently. Preclinical MRI- and dedicated MR-microscopy (MRM) scanners already allow for microimaging and MRM (1-256 μm) but lack a sensible spatial resolution phantom for QC and performance improvements in hardware, pulse-sequencing and MRprotocols. In most scientific MRI articles, the spatial resolution is characterized by the ps, though this measurement parameter only limits the actual resolution. Methods: Here the Modulation-Transfer-Function (MTF) is used as evaluation concept for the determination of the spatial resolution in MRM using simple intensity profiles. The resolution limit is defined using a critical modulation-level. In approaching visual impressions on spatial resolution an additional criterion derived from the Modulation-depth-to-Noise-Ratio (MNR) is proposed. A practical method for assessment based on a concrete phantom design and its realization is shown. Results: The phantom design consists of several sets of fine grids, specifically featuring high structural anisotropy for optimum SNR and CNR, with different spatial periods ranging from a1 = 256 μm down to a8 = 2 μm, not only for a quick visual qualitative check, but also for quantification of resolution using the MTF for two different spatial encodings in two orthogonal in-plane directions. The challenging demands on the manufacturing technology especially with regard to the aspect-ratio are approached using Deep-X-Ray-Lithography (DXRL) relying on the high brilliance of Synchroton-radiation. Smallest grid plates with width of 4 μm corresponding to 125 line pairs/mm at a plate depth of 100 μm were achieved. Discussion: MR-microscopic images, originating from a microscopy insert on a human UHF-MR-scanner, were used for demonstration of the evaluation process with two independent resolution-criteria. The developed prototype offers unique possibilities for quantitative resolution QC on UHF human and preclinical MR-scanners. Such a resolution-phantom might be very important for the improvement of MR-pulse-sequences, MR-protocols and even hardware. In principle the phantom can also be used for other microscopic imaging-modalities as for instance μCT and Optical-Coherence-Tomography (OCT).